1989
DOI: 10.1016/0014-5793(89)81534-0
|View full text |Cite
|
Sign up to set email alerts
|

Participation of acid phospholipids in protein translocation across the bacterial cytoplasmic membrane

Abstract: Recent observations confirm the participation of acid phospholipids in protein translocation. The hypothesis proposed coupled protein translocation with transmembrane movement of acid phospholipids, their metabolism as a precursor of cell envelope components and recycling. These factors ensure the unidirectional vector value of the secretion, restoration of the membrane site competent for protein translocation and its self-organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Probably, peptide insertion into the membrane across the lipid bilayer is more likely because the lipid constituent of the membrane is more flexible and, consequently, offers more available microenvironment for peptide insertion than the membrane protein. Besides, it is confirmed by the experimental data known by now, including our own, and also by the concepts developed on their basis ( 17,18). As far as the participation of proteins in these processes is concerned, they can play an important role in protein targeting from Downloaded by [Rutgers University] at 16:53 13 April 2015 cytoplasm to the membrane surface, as well as in providing effetive interaction between SP and PL.…”
Section: Molecular Modeling Of Signal Peptide Interaction With the Mesupporting
confidence: 72%
See 2 more Smart Citations
“…Probably, peptide insertion into the membrane across the lipid bilayer is more likely because the lipid constituent of the membrane is more flexible and, consequently, offers more available microenvironment for peptide insertion than the membrane protein. Besides, it is confirmed by the experimental data known by now, including our own, and also by the concepts developed on their basis ( 17,18). As far as the participation of proteins in these processes is concerned, they can play an important role in protein targeting from Downloaded by [Rutgers University] at 16:53 13 April 2015 cytoplasm to the membrane surface, as well as in providing effetive interaction between SP and PL.…”
Section: Molecular Modeling Of Signal Peptide Interaction With the Mesupporting
confidence: 72%
“…However, recent studies showed the existence of a close link between the secretory process and composition, turnover and physicochemical state of membrane phospholipids (16)(17)(18), and a number of hypotheses of molecular mechanism of involvement of these compounds in the secretory process were proposed (16)(17)(18)(19). The fact that, besides the signal peptide, relatively small molecules of phospholipids play an important role in the process of translocation, opened a principal possibility for the elucidation of the molecular mechanism of translocation by the theoretical methods of structural analysis.…”
Section: Kajava Eta/mentioning
confidence: 99%
See 1 more Smart Citation
“…Speculation still exists, however, as to whether this translocator forms a proteinaceous 'pore' through which unfolded polypeptides are sequestered across the membrane as there is considerable evidence supporting a direct role for membrane lipids in protein translocation (Nesmeyonova & Bogdanov, 1989;de Vrije, et al, 1990;Tai, 1990). Unlike E. coli, little is known about the secretion process in Gram-positive bacteria, though recent studies with B. subtilis have led to the isolation of secY/prlA and secA homologues (Suh et al, 1990;Sadaie et al, 1991).…”
Section: Protein Secretion In Prokaryotesmentioning
confidence: 99%
“…Phospholipids are a candidate for metabolites which are common for protein secretion and envelope biogenesis. As components of the cytoplasmic membrane, they not only form the barrier of permeability for many substances but also, being a microenvironment for many proteins and possessing metabolic and structural dynamicity, phospholipids are involved in many transmembrane processes [9][10][11][12][13]. In particular, anionic phospholipids (APL) provide optimal conditions for the functioning of protein components of secretory machinery and participate in secretion initiation through interaction with the signal peptide [14][15][16].…”
Section: Introductionmentioning
confidence: 99%